Acute nitric oxide synthase inhibition and endothelin-1-dependent arterial pressure elevation - Rapoport, Robert (Frontiers in Pharmacology, 2014)
Key evidence that endogenous nitric oxide (NO) inhibits the continuous, endothelin (ET)-1-mediated drive to elevate arterial pressure includes demonstrations that ET-1 mediates a significant component of the pressure elevated by acute exposure to NO synthase (NOS) inhibitors. This review examines the characteristics of this pressure elevation in order to elucidate potential mechanisms associated with the negative regulation of ET-1 by NO and, thereby, provide potential insight into the vascular pathophysiology underlying NO dysregulation. We surmise that the magnitude of the ET-1-dependent component of the NOS inhibitor-elevated pressure is 1) independent of underlying arterial pressure and other pressor pathways activated by the NOS inhibitors and 2) dependent on relatively higher NOS inhibitor dose, release of stored and de novo synthesized ET-1, and ETA receptor-mediated increased vascular resistance. Major implications of these conclusions include: 1) the marked variation of the ET-1-dependent component, i.e., from 0-100% of the pressure elevation, reflects the NO-ET-1 regulatory pathway. Thus, NOS inhibitor-mediated, ET-1-dependent pressure elevation in vascular pathophysiologies is an indicator of the level of compromised/enhanced function of this pathway; 2) NO is a more potent inhibitor of ET-1-mediated elevated arterial pressure than other pressor pathways, due in part to inhibition of intravascular pressure-independent release of ET-1. Thus, the ET-1-dependent component of pressure elevation in vascular pathophysiologies associated with NO dysregulation is of greater magnitude at higher levels of compromised NO.